Dreams and illusions in adolescents with terminal cancer. Issue 6 (December 2018) - Veneroni, Laura; Ferrari, Andrea; Proserpio, Tullio; Pagani Bagliacca, Elena; Podda, Marta; Massimino, Maura; Alfredo Clerici, Carlo
Being diagnosed with cancer in adolescence generally has important emotional consequences: adolescent cancer patients need to be seen as special cases with particular medical and psychosocial needs. This is especially true when a young patient is faced with a progressive, incurable disease. Herein, we report the story of a 17-year-old girl with a metastatic refractory soft tissue sarcoma who tells her dream to the psychologist of the ward. Telling this narrative is the opportunity to discuss the complex topic of how adolescent cancer patients adapt to the terminal stage of their disease; for example, the patient needs to talk to someone about their fear of dying; the healthcare operators need to be able properly listen and communicate; the patient's trust in the future despite their clinical condition; the necessity to leave space for hope; the useful role of the imagination sphere; the issue of whether and how to tell a person who is terminally ill the truth about their condition.